2020
DOI: 10.1590/1678-4162-12116
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of ARFI elastography in the evaluation of canine prostatic alterations detected by b-mode and Doppler Ultrasonography

Abstract: The aim of this study was to assess the applicability of ARFI elastography for the complementary diagnosis of canine prostatic alterations. Twenty-two healthy dogs and 45 with prostatic alterations were diagnosed by the association of general and specific physical exams. Complete blood count, B-mode and Doppler ultrasound were performed. For the elastography study, tissue homogeneity and deformity were verified using the elastogram, and the shear velocities of the left and right lobes of all prostates were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
(17 reference statements)
1
4
0
Order By: Relevance
“…In healthy dogs, the prostate has been described with a homogeneous and soft/middle soft appearance, with increasing stiffness in case of disorders, similar to what is currently observed in human medicine (Cintra et al, 2020;Correas et al, 2013;Domosławska et al, 2018;Feliciano et al, 2015;Grosu et al, 2019;Jeon et al, 2015).…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…In healthy dogs, the prostate has been described with a homogeneous and soft/middle soft appearance, with increasing stiffness in case of disorders, similar to what is currently observed in human medicine (Cintra et al, 2020;Correas et al, 2013;Domosławska et al, 2018;Feliciano et al, 2015;Grosu et al, 2019;Jeon et al, 2015).…”
Section: Introductionsupporting
confidence: 68%
“…ARFI elastography is an imaging technique that provides quantitative and qualitative measurements of tissue stiffness based on short, high‐intensity acoustic pulses to deform the tissue and create a static greyscale map (elastogram) that represents the relative stiffness of the tissue in the imaged region. The elastogram can then be compared to the corresponding conventional US image and, in general, lighter areas represent more deformable tissue compared with darker areas (Cintra et al, 2020; Sigrist et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…proposed for the examination of nonfocal alterations of the testis, aiding in infertility aetiology determination [26,163,164]. In veterinary medicine, studies have been conducted to apply UEl to canine and feline normal and pathological conditions in various organs, including the spleen, liver, kidney, prostate [165][166][167][168], adrenal glands [169], skin [170], lymph nodes [133,171], pancreas [172], small intestine mucosa [173], and placenta [174]. The qualitative study on foetal lungs and liver during the final days of intrauterine development were also reported, revealing tissue stiffness changes [175].…”
Section: Normal Findingsmentioning
confidence: 99%
“…A study of dogs assessed their tissue homogeneity, deformation capacity, and shearwave velocity, and it revealed that the shear-wave velocity was significantly higher in prostatic alterations when compared to normal prostatic tissue [10]. The same authors suggested that a velocity greater than 2.35 m/s is potentially associated with malignant lesions.…”
Section: Prostate and Testesmentioning
confidence: 99%
“…Several studies have used elastography for assessing hepatic fibrosis in humans as a preliminary assessment before tissue biopsies or for predicting and detecting malignancy [5,7], as well as for assessing acute and chronic kidney diseases [8]. In veterinary medicine, recent studies have explored elastography for evaluating the prostate [9][10][11], liver [12], and kidneys in dogs and cats [2,9], as well as for assessing hepatic fibrosis [13], lymph nodes [2,[14][15][16][17][18][19][20][21][22], and mammary neoplasms [1,4,[23][24][25]. Elastography has been shown to be a promising diagnostic method in the evaluation and prediction of neoplasm malignancy, mainly due to its safety and low invasiveness [1].…”
Section: Introduction To Elastographymentioning
confidence: 99%